Volume 5: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1998
DOI: 10.1115/98-gt-583
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mistuning Characteristics of Bladed Disks From Free Response Data

Abstract: The focus of the present investigation is on the estimation of the dynamic properties, i.e. masses, stiffnesses, natural frequencies, mode shapes and their statistical distributions, of turbomachine blades to be used in the accurate prediction of the forced response of mistuned bladed disks. As input to this process, it is assumed that the lowest natural frequencies of the blades alone have been experimentally measured, for example in a broach block test. Since the number of measurements is alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This technology has intensively been studied in the framework of the linear dynamic analysis (see for instance, [4,5,6,7,8,9,10,11,12,13,14]), for which the mistuning effects have been modeled using either parametric probabilistic approaches (see for instance, [15,16,17,18,19]), or using the nonparametric probabilistic approach ( [20,21,22]), and for which the optimization of alternating patterns has been studied (see for instance, [23,24,25,26]).…”
Section: Introductionmentioning
confidence: 99%
“…This technology has intensively been studied in the framework of the linear dynamic analysis (see for instance, [4,5,6,7,8,9,10,11,12,13,14]), for which the mistuning effects have been modeled using either parametric probabilistic approaches (see for instance, [15,16,17,18,19]), or using the nonparametric probabilistic approach ( [20,21,22]), and for which the optimization of alternating patterns has been studied (see for instance, [23,24,25,26]).…”
Section: Introductionmentioning
confidence: 99%
“…The issue is then how to model the variations of structural properties (mistuning) to achieve this goal. As pointed out by Mignolet et al [22] among others, assuming small perturbations, an accurate knowledge of all structural parameters is not always necessary to get good predictions of global responses. Rather, the identification of modal characteristics can be sufficient.…”
Section: Mistuning Representationmentioning
confidence: 99%
“…To solve the final mistuning problem defined by (22), a least square fit strategy is used (which is quite usual in model updating techniques and was also used in other mistuning identification techniques [13]). The aim is to determine parameters p i , so they are isolated in a vector p:…”
Section: Identification Of Mistuning Parametersmentioning
confidence: 99%
“…In this case, blade eigenfrequencies are mistuned through the stiffness parameters but the corresponding eigenmodes remain unchanged with respect to the tuned case. Recently, Mignolet et al [13,14] introduced a probability model which is experimentally identified using the maximum likelihood principle in order to include blade-modal-shape mistuning or not. This model exhibits differences with respect to the parametric probability model currently used.…”
Section: Introductionmentioning
confidence: 99%